Pengaruh Campuran Jenis ZPT Alami dan Lama Perendaman Terhadap Perkecambahan Benih Pinang (Areca Catechu L.) - Sulhijah, Sulhijah; Syukri, Syukri; Saputra, Iwan; Ridha, Rizky (Universitas Trunojoyo Madura, 2024)
In providing areca seeds, there is an obstacle that often arises, namely the nature of dormancy so that it takes only a little time to germinate. This condition can be overcome by administering natural ZPT such as young coconut water, shallots, bamboo shoots and banana stems. The aim of the research was to determine the ability of a mixture of natural PGR types and soaking time to stimulate the germination of areca nut seeds. The research was conducted from June to August 2023, the experimental design was RAK factorial pattern consisting of 2 factors: The first factor was a mixture of natural PGR, Coconut Water (AK), Shallot Extract (BM), Banana Weevil Extract (BP), and Bamboo Shoot Extract ( RB) with a composition of 5 levels, namely: Z0: Air (control); Z1 : AK + BP; Z2 : BM + AK + RB; Z3 : RB + BP + BM; Z4 : AK + BM + BP + RB. The second factor of soaking time consists of 3 levels, namely: L1: 18 hours; L2: 24 hours; L3 : 30 hours. The research results showed that the treatment of a mixture of natural PGR types had a very significant effect on the vigor index and root length. The long soaking treatment had a very significant effect on the length of the tuna, but had a significant effect on the germination time and speed of seed growth. There was no interaction between the two treatments. The best natural PGR mixture is recommended to use Z2, Z3 and Z4 treatment with L2 soaking time